Supplementation of Acqua Lete® (Bicarbonate Calcic Mineral Water) improves hydration status in athletes after short term anaerobic exercise - Brancaccio Paola; Limongelli Francesco; Paolillo Iride; D'Aponte Antonio; Donnarumma Vincenzo; Rastrelli Luca (Taylor & Francis Group, 2012)
Abstract Background Experimental studies suggest that mineral waters with high concentrations of calcium and bicarbonate can impact acid-base balance. The purpose of this study was to test the effect on acid-base balance and specific urine gravity, of a bicarbonate calcic mineral water (Acqua Lete®) compared to a minimally mineralized water. Methods 88 amateur male athletes underwent two experimental trials with a modified Wingate test: the first was carried out without hydration (Control Test, Test C, n = 88); the second was carried out after one week of controlled hydration (Test with hydration, Test H, n = 88), with 1.5 L/day of a very low mineral content water (Group A, n = 44) or 1.5 L/day of Acqua Lete® (Group B, n = 44). Measure of body temperature, bioimpedance analysis, muscular ultrasound, and urinalysis were taken before (t0), immediately after (t1), 5' (t2), and 30' (t3) after exercise. Results Hydration results in a decreased core temperature; muscular ultrasound showed increased muscle thickness after exercise related to content of body water. Regarding urinalysis, in test H, we found in both groups after exercise a significant decrease of specific urine gravity with significantly lower levels in Group B. We also found a significant increase of pH in the same Group B. Conclusions In conclusion all the athletes hydrated with Acqua Lete® showed a positive impact on hydration status after anaerobic exercise with significant decrease of specific urine gravity and a positive effect on pH.